A unique presentation of ectopic thyroid, a case report. (2016) - Allen, Erika; Alzeerah, Masoud; Tsiao, Stevenson; Aydin, Nail; Misra, Subhasis
Highlights: Previous description of ectopic thyroid tissue has not included point tenderness as a presenting symptom. Ectopic Thyroid shoudl be included in teh differential diagnosis of point tenderness with an associated mass or lesion on imaging. Management of both symptomatic ectopic thyroid and esophageal perforation with periesophageal abscess is surgical intervention. It is important to perform due diligence in the work up of a patient without compromising the patient's safety to do so. Abstract: Introduction: This case presents a painful ectopic thyroid, an unusual presentation, in an atypical location. The patient's history of an ingested fish bone, her acute presentation, and inconclusive imaging, made this case a diagnostic dilemma. Presentation of case: 61-year-old female presented with acutely worsening history of left throat pain and dysphagia after swallowing a fish bone. CT scan showed a foreign body in the anterior wall of the cervical esophagus. EGD studies were inconclusive. Surgical exploration identified and excised a multinodular cystic lesion without connection to esophageal lumen. Pathology described multinodular thyroid parenchyma with chronic inflammation and no evidence of malignancy. No foreign body was located. Discussion: Based on the patient's history, imaging, and acute presentation, an esophageal perforation with abscess formation was the most likely diagnosis. Surgical exploration was the necessary intervention for this patient's acute symptoms as both a diagnostic and therapeutic tool. The diagnosis of ectopic thyroid tissue from pathology of the excised cystic lesion was unexpected, as the location of tissue and the painful presentation are not typical characteristics of ectopic thyroid tissue. Management of the this case illustrates the dilemma faced in determining the appropriate work up for a patient, without compromising the patient's safety. Conclusion: Though painful presentation and this case's location are rare, ectopic thyroid tissue should be included in the differential diagnosis of point tenderness with an associated lesion on imaging.